Zakat as a Moderating Variable of the Effect of Taxes on Market Equilibrium : Penelitian - Ani Pujiati; Saefudin Zuhri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is a quantitative study with an explanatory approach, an approach that uses reference research as the main material for creating hypotheses and proving both hypotheses in this study. The data used in this study is primary data obtained by researchers from the websites of the National Zakat Agency, the Central Statistics Agency, and the Ministry of Finance. The data is in the form of annual data from 2019 to 2024. The existing data is analyzed using smart PLS 4.0 software